Experts by Experience: Qualitative Evaluation of Adolescent Participation in the Development of a Technological Intervention to Prevent Youth Suicide in Chile - Schilling, Sara Hamilton; Carreño, Alejandra; Tapia, Eric; Mascayano, Franco; Pitronello, Romina; Santander, Felipe; Jorquera, María José; Burrone, María Soledad; Alvarado, Ruben Vladimir (Frontiers in Psychiatry, 2021)
Adolescent suicide is a pressing problem in Chile that has not yet been sufficiently addressed, as suicide rates have stagnated in recent years. One possible explanation could be linked to the adult-centered paradigm that continues to prevail in relation to adolescent health initiatives. In light of this, programs that seek to promote youth mental health should consider incorporating adolescents in the design process using participatory methodologies, to ensure that these initiatives are well-suited for the population. In line with this recommendation, a group of seven adolescents, 13 to 20 years of age, were incorporated into a research team to actively guide the design, development, and validation of a technology-based intervention, known as Project Clan, which was piloted to reduce adolescent suicide in schools in Chile. This group was known as the “Group of Experts,” in acknowledgement of their role as experts by experience on adolescence. A qualitative case study was conducted to explore their lived experiences, though semi-structured individual in-depth interviews with six members of the Group. Results showed that the adolescents had a high level of interest in mental health and had experienced problems of their own or accompanied friends who were struggling, which motivated their participation in the study. They had a critical view of the previous interventions they had received through educational institutions, and valued their role in the promotion of their peers’ mental health through the Group of Experts. They also highlighted the importance of creating tools that complement their daily lives and provide an alternative to existing social networks, by respecting their anonymity, providing a secure place for divulgation and self-expression, and facilitating access to professional support. We conclude that programs that address issues which affect adolescents should incorporate adolescents in the decision-making and design processes to ensure the acceptability and effectivity of their interventions.